Total sugar analysis: Periodic Table of Food Initiative - Conner, Alexandria (2024)
This Standard Operating Procedure (SOP) describes a method to extract total sugar, measured as glucose, fructose, sucrose, lactose, maltose and isomaltose, from animal and plant samples. The samples are diluted in 75% organic solution with an added internal standard mixture. The sugar components are separated on a Water BEH Amide column and detected by the Agilent Triple Quadrupole LC/MS.